2021
DOI: 10.3390/ijerph18115834
|View full text |Cite
|
Sign up to set email alerts
|

Use of Respiratory Protection Devices by Medical Students during the COVID-19 Pandemic

Abstract: The use of face masks has assumed a leading spot among nonspecific prevention measures during the coronavirus pandemic. The effectiveness of this protective measure depends on the specifics of individual use. The purpose of our study was to analyze the use of respiratory protective equipment (RPE) by medical students during the COVID-19 pandemic. The evaluation of face mask use was based on the results of a survey of medical students at Sechenov University. There were 988 participants in the study: 97.5% used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 51 publications
1
8
1
1
Order By: Relevance
“…[11] In study conducted by Ekaterina A Shashina et al revealed that 89.1% of their participant used disposable medical face masks, 27.4% used reusable cloth face masks and 13.2% used respirators. [12] But in our study, cloth mask (91%) was more popular among the participants followed by respirators (N95) (88%), and 70% of the study participants would use single use surgical mask and 23% preferred using cloth mask.…”
Section: Discussioncontrasting
confidence: 57%
“…[11] In study conducted by Ekaterina A Shashina et al revealed that 89.1% of their participant used disposable medical face masks, 27.4% used reusable cloth face masks and 13.2% used respirators. [12] But in our study, cloth mask (91%) was more popular among the participants followed by respirators (N95) (88%), and 70% of the study participants would use single use surgical mask and 23% preferred using cloth mask.…”
Section: Discussioncontrasting
confidence: 57%
“…The suboptimal FM use knowledge could be related to the students’ lack of interest in exploring the proper use of FM because most of them had learned how to use personal protective equipment. This lack of interest among health care students could also be associated with the lack of interest among students to read manufacturer instructions on proper FM use and decontamination [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…When the populace began receiving mass vaccinations, wearing face masks was still crucial as a precaution to reduce the chance of contracting the coronavirus (Lesser & Whittaker, 2021). This is owing to the virus's fast propagation of new strains that are more infectious than the original (Shashina et al, 2021). However, it is possible that the pandemic will continue to spread despite the creation of specific COVID-19 prophylaxis.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is possible that the pandemic will continue to spread despite the creation of specific COVID-19 prophylaxis. Where, it is challenging to vaccinate a significant section of the population in a short time for a variety of actual and perceived reasons: contraindications, chronic conditions, and certain individuals' antivaccination attitudes must all be considered (Lesser & Whittaker, 2021;Shashina et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation